2018
DOI: 10.1002/da.22787
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between moral injury appraisals, trauma exposure, and mental health in refugees

Abstract: These results suggest that there may be subtypes of moral injury appraisals that are associated with different mental health outcomes. These findings have potential implications for designing treatments that address the psychological impact of the refugee experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
101
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(121 citation statements)
references
References 66 publications
(120 reference statements)
15
101
5
Order By: Relevance
“…Hoffman et al (2018) found support for two ways that traumatic events could be appraised as moral violations in a diverse refugee population: transgression by others (MI-Other) and transgressions by oneself (MI-Self). In both populations, PTSD symptoms were associated with MI-Other but not MI-Self appraisals (Bryan et al, 2015;Hoffman et al, 2018), indicating that perceived moral violations enacted by the self are less likely to be associated with PTSD. In contrast, results have been less consistent across military samples for symptoms such as anger, depression and suicidal ideation (Bryan et al, 2015;Bryan, Bryan, Morrow, Etienne, & Ray-Sannerud, 2014).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Hoffman et al (2018) found support for two ways that traumatic events could be appraised as moral violations in a diverse refugee population: transgression by others (MI-Other) and transgressions by oneself (MI-Self). In both populations, PTSD symptoms were associated with MI-Other but not MI-Self appraisals (Bryan et al, 2015;Hoffman et al, 2018), indicating that perceived moral violations enacted by the self are less likely to be associated with PTSD. In contrast, results have been less consistent across military samples for symptoms such as anger, depression and suicidal ideation (Bryan et al, 2015;Bryan, Bryan, Morrow, Etienne, & Ray-Sannerud, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…Appraisals that events have violated important moral beliefs have been found to be associated with greater depression, PTSD, anger, guilt and shame in a military sample, above and beyond trauma exposure (Lancaster & Erbes, 2017). Similarly, moral injury appraisals have been found associated with PTSD, anger and depression above and beyond trauma exposure in a refugee sample (Hoffman, Liddell, Bryant, & Nickerson, 2018). Therefore, understanding how the mechanism by which moral injury links these outcomes to traumatic experiences is crucial for designing effective interventions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DAR-5 measure (21) has demonstrated robust convergent, concurrent and discriminant validity. In addition, the recommended cut off, aligned with the 75 th percentile of the State Trait Anger Expression Inventory-2 (STAXI-2;(20)), has been associated with psychological distress and functional impairment (22,23) and utilized in numerous studies (31)(32)(33).…”
Section: Problematic Angermentioning
confidence: 99%